Inclusive da’wa on Indonesian people: The role of people in the view of Auguste Comte - Iskandar Iskandar; Nurhakki Anshar; Afidatul Asmar (Jurnal Ilmu Dakwah, 2022)
Purpose - The purpose of this research is to find out the reasons why inclusive da’wa is needed in Indonesian society, to find out the impact of inclusive da’wa material on the Indonesian's lives, and to find out the opportunities and obstacles for implementing inclusive da'wah in Indonesia.Method - The research’s type is qualitative research with a multidisciplinary approach, so the data collection use observation method and documentation with Auguste Comte's positivism theory is then analyzed and a conclusion is drawn.Result - The results showed that inclusive da’wa is required in Indonesian society because Indonesian society is plural, and consisting of diversity so in spreading friendly Islamic teachings it is not only possible to implement it in theory which is based on Alquran and Hadith. On the other hand, knowledge is required as an approach to seeing Indonesian society.Implication - The impact of inclusive da’wa material on the people's lives in Indonesia has influenced changing people's mindsets. Significantly, now society, in general, can understand differences as a necessity that their existence must be respected.Originality – This article examines inclusive Da’wa referring to Auguste Comte.***Tujuan – Tujuan dari penelitian ini adalah untuk mengetahui alasan mengapa da’wa inklusif diperlukan dalam masyarakat Indonesia, untuk mengetahui dampak materi da’wa inklusif terhadap kehidupan bangsa Indonesia , dan untuk mengetahui peluang dan hambatan pelaksanaannya . da’wa inklusif di Indonesia.Metode - Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan multidisiplin, sehingga pengumpulan data menggunakan metode observasi dan dokumentasi dengan teori positivisme Auguste Comte kemudian dianalisis dan ditarik suatu kesimpulan.Hasil - Hasil penelitian menunjukkan bahwa da’wa inklusif diperlukan dalam masyarakat Indonesia karena masyarakat Indonesia adalah plural, terdiri dari keragaman sehingga dalam menyebarkan ajaran Islam ramah tidak hanya mungkin untuk menerapkannya dalam teori yang didasarkan pada al-quran dan hadits. . Namun di sisi lain, pengetahuan dibutuhkan sebagai pendekatan dalam melihat masyarakat Indonesia.Implikasi - Dampak materi da’wa inklusif terhadap kehidupan masyarakat di Indonesia telah membawa pengaruh terhadap perubahan pola pikir masyarakat. Secara signifikan, kini masyarakat pada umumnya mampu memahami perbedaan sebagai keniscayaan yang harus dihormati keberadaannya.Orisinalitas – Artikel ini mengkaji da’wa inklusif yang mengacu pada Auguste Comte.